An all-solid-state fiber-type solar cell achieving 9.49% efficiency. Issue 26 (16th June 2016) - Qiu, Longbin; He, Sisi; Yang, Jiahua; Jin, Feng; Deng, Jue; Sun, Hao; Cheng, Xunliang; Guan, Guozhen; Sun, Xuemei; Zhao, Haibin; Peng, Huisheng
Abstract : A fiber-type perovskite solar cell is fabricated by wrapping a conducting carbon nanotube sheet onto a perovskite crystal-deposited strip electrode. Abstract : Flexible and wearable solar cells represent a promising direction in the advancement of next-generation energy-harvesting electronics. However, the solar cells in a planar structure cannot meet the requirements of complicated deformations. On the other hand, solar cells based on the one-dimensional structure attract increasing interest as they can stably work under both bending and twisting. Here, a family of fiber-type perovskite solar cells has been designed with impressive photovoltaic performance. They exhibit a high power conversion efficiency of 9.49% that is stable under both bending and twisting. A combination of large crystals of perovskite and aligned carbon nanotube sheets contributes to their excellent properties. Due to their unique fiber shape, they can be further woven into flexible and lightweight power textiles that are promising as the next-generation portable and wearable electronics.